Desain Kurikulum Pembelajaran Pendidikan Agama Kristen yang Relevan dengan Perkembangan Peserta Didik Abad ke-21 - Nofita Rudiani Asbanu; Hemi Damnosel Bara Pa (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
The 21st century has brought significant challenges and transformations to the world of education, demanding a curriculum that integrates critical thinking, creativity, collaboration, and communication skills (4C), as well as digital literacy and ethical responsibility. This study aims to explore a contextual curriculum design for Christian Religious Education (PAK) that is relevant to the holistic development of students in today's era. Using a qualitative descriptive method based on literature review, the research analyzes theoretical concepts and previous studies related to contextual and character-based Christian education. The findings show that a transformative and contextual PAK curriculum must address not only the cognitive dimension but also affective and psychomotor aspects, rooted in real-life experiences and local cultural contexts. The role of teachers as facilitators, curriculum designers, and role models is central to effective implementation. This study provides implications for curriculum development policies, teacher training, and further research in applied classroom settings.